Peningkatan Kemampuan Menyusun Silabus Mulok Kebencanaan Melalui Pelatihan Bagi Guru Kelas Atas - Marsono, Marsono (Universitas Muhammadiyah Magelang, 2019)
The purpose of this study is to improve the ability of upper class teachers to compile the Mulok Disaster syllabus in the Argopurno Cluster, Salaman District. The subjects of this study were 16 upper-class teachers, who served in 5 elementary schools. While the object of research is to improve the ability of upper class teachers to compile the Mulok Disaster syllabus. This school action research was carried out in 2 cycles, each cycle consisting of 3 meetings. Data collection is carried out through observation, interviews, and document studies. Data analysis is carried out by document assessment, data presentation and conclusion drawing, with indicators of minimum success reaching an average value of 80. The results of the study indicate that the ability of teachers in the initial conditions has not been able to compile the Mulok Disaster syllabus, in cycle I was able to compile a syllabus with the highest value 83, the lowest is 64, and the average value is 74. In cycle II it has increased with the highest value of 88, the lowest 78, and an average value of 83. The application of training methods can improve the ability of classroom teachers to compile the Mulok Disaster syllabus in the Argopurno Cluster, Salaman District.